Classification of coronoid process fractures: A pending question - Wang, Daofeng; Li, Jiantao; Xu, Gaoxiang; Zhang, Wupeng; Li, Li; Tang, Peifu; Zhang, Licheng (Frontiers in Surgery, 2022)
Ulna coronoid fracture is a complicated elbow injury. Comprehensive classification of coronoid fracture can assist diagnosis, guide treatment, and improve prognosis. Existing coronoid fracture classifications are insufficient to interpret all fracture patterns. The coronoid fracture classification is associated with elbow-specific trauma patterns. Coronoid fractures are often associated with other elbow injuries, commonly with radial head fractures, which makes the clinical strategies inconsistent and prognosis poor. The current fracture classifications do not contain information about combined injuries. Preservation of ulnohumeral joint contact after trauma is critical to elbow mechanical and kinematic stability. Important fracture types for treatment include terrible-triad injuries and anteromedial facet fractures. Open reduction and internal fixation of these two fractures should be conducted when marked displacement of the fragment, elbow instability under stress, and complicated associated injuries. The current surgical tactics based on classifications are still controversial.